Anomalous DOC signatures reveal iron control on export dynamics in the Pacific Southern Ocean - Lopez, Chelsea N.; Hansell, Dennis A. (Frontiers in Marine Science, 2023)
Here we shed light on two mechanisms that stimulate deep particle export via upper-ocean iron fertilization in the Southern Ocean: deep frontal mixing and melting of sea ice. We present data collected a decade apart in the Pacific sector of the Southern Ocean when, serendipitously, seasonal Antarctic ice melt was anomalously low (2008) and anomalously high (2017). In 2008, the low ice melt year, we concluded that vertical mixing of iron into the euphotic zone via deep-mixing fronts was the primary stimulant of export that reached depths of 1500 meters. This process was evidenced by localized enhancements of dissolved organic carbon (DOC) concentrations up to 4 µmol kg-1 beneath seven branches of fronts embedded within the Antarctic Circumpolar Current (ACC). We used these enhanced DOC concentrations in the bathypelagic as primary indications of the depths and locations of recent export, as it is a logical residue of such. In 2017, the year in which sea ice melt was anomalously high, we concluded that the main driver of a widespread export event to the seafloor was the lateral influx of iron within the melt. Indications of this event included substantial enhancements of DOC concentrations (2 - 6 µmol kg-1), elevated beam attenuation, and enhanced surface iron concentrations associated with a layer of low salinity water at a nearby station. Further, significant deficits of upper ocean silicic acid during the 2017 occupation indicated that deep export was likely stimulated by an iron-fueled diatom bloom. This analysis highlights the impact of iron supplied from frontal vertical mixing and sea ice melt on export and ultimately for long-term carbon sequestration in the Southern Ocean, as well as the utility of deep DOC enrichments as signatures of particle export. Understanding the impact that ice melt events have on carbon export is crucial given that anomalous events are occurring more often as our climate changes.